Analisis Penanaman Karakter dalam Pembelajaran Matematika di SD - Wahyuni, Sri; Darsinah, Darsinah; Desstya, Anatri (Muróbbî: Jurnal Ilmu Pendidikan, 2024)
Abstract: This research aims to analyze the character values ​​instilled in mathematics learning activities in elementary school. This research includes qualitative descriptive research with a case study approach, which was carried out at SDN Somomorodukuh 2, Plupuh, Sragen. The subjects of this research were 9 students in class IV. The object of the research carried out is character cultivation in mathematics learning. In testing the validity of the data using triangulation techniques. Data collection uses observation, interviews and documentation methods. There are three steps in the research carried out, including: condensing data, presenting data, and drawing conclusions or verification.The results of the research show that there are 12 character values ​​contained in mathematics learning, including:disciplined, religious, love of the country, communicative,, likes to read, curious, responsible, hard working, independent, honest, democratic, appreciates achievement.